Effect of B on microstructure and properties of joints brazed by In-situ Ag-Cu-Zn-Sn filler metal with high Sn content. (1st November 2022) - Zhong, Sujuan; Li, Yunpeng; Shi, Yinkai; Qin, Jian; Yu, Hua; Cui, Datian; Long, Weimin
Abstract: The copper brazed joints were obtained by induction brazing using in situ synthetic high Sn content silver filler metals with different B contents and the effect of element B on the wettability of filler metals and microstructure and mechanical properties of the joints were studied. With the addition of element B, the spreading area of the filler metals on the copper increases. The microstructure of the joints mainly consists of silver-based solid solution and copper-based solid solution, and the distribution of silver-based solid solution in the brazing seam becomes dispersed with the addition of B. The width of the brazing seam increases significantly with the increase in B content. Meanwhile, the B element was mainly distributed in the Ag-based solid solution. The tensile strength firstly increased and then sharply decreased with B added. The maximum average tensile strength of 206.83 MPa was obtained with a 2% addition of B and the joint fracture pattern is a brittle fracture.